Peningkatan hasil belajar pemecahan masalah matematika melalui model problem based learning berbasis karakter - Dwi Susriyati; Siti Yurida (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2019)
This research aims to increase the learning outcomes of mathematics by applying character-based PBL models in 5th grade of SDN Salatiga 01. There were 43 students, but only 44,2% (19 students) got score above minimum campletenness criteria (KKM). While 55,8% (21 students) got score under the KKM. the type of this research was action reseach by using stringer model. Data collection instruments used question instruments, observation sheets, and documentation. This research held in two cycles with three stages. The stages consist off look, think, and act. The technique of data analysis used comparative desciptive technique. The subjects of the research were students in 5th grade of SDN Salatiga 01. The result of completeness mathematics learning outcome in the first cycle was 62,8% and in the second cycle was 76,7%. Student’s mathematics learning outcomes in the second cycle were better than the mathematics learning outcomes in the first cycle. Based on the result, applying character-based PBL models increased the learning outcomes of mathematics in 5th grade of SDN Salatiga 01.